Students’ Perception toward English Online Learning - Elza Pebriani; Puji Siswanto; Arief Styo Nugroho (English Education, Linguistics, and Literature Journal, 2022)
Abstract: This research aimed at knowing the students' perception towards English online learning during Covid-19 pandemic at SMAN 1 Cipanas. This research uses qualitative method with a case study approach. The data were collected through interviews with students. Out of 38 students, researcher only interviewed 13 people of XI MIPA 3 at SMAN 1 Cipanas participated in this research. The result of this research was presented descriptively in order to reveal the students' perception. The results of this study found positive and negative perceptions. Some students stated that learning English while at home was quite effective, because it is the only way out to continue learning online while the Covid-19 pandemic is still in Indonesia, so they can still learn even though it is not directly at school. And some argue that online learning English is not effective, because there are obstacles such as difficult signals, bored, sometimes there are students who do not have a quota and limited space for students to talk to the teacher